2009
DOI: 10.1002/lary.20495
|View full text |Cite
|
Sign up to set email alerts
|

Surgical techniques for the treatment of nasal valve collapse

Abstract: A variety of focussed surgical techniques are described to deal with nasal valve collapse. We could find no randomized controlled trials on nasal valve surgery. Research in nasal valve surgery is frequently driven by technical description of surgical technique rather than the establishment of evidence of long-term patient benefit. Although our understanding of the role of the nasal valve in the pathophysiology of nasal obstruction has improved vastly, the myriad of surgical techniques described perhaps reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Similar findings and conclusions were presented in another systematic review by Spielman et al 10 The review reported that nasal valve surgery research is too focused on the technique rather than patient outcomes. Additionally, the review pointed out the deficiencies in the use of objective measures for assessing nasal airflow to evaluate the efficacy of treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings and conclusions were presented in another systematic review by Spielman et al 10 The review reported that nasal valve surgery research is too focused on the technique rather than patient outcomes. Additionally, the review pointed out the deficiencies in the use of objective measures for assessing nasal airflow to evaluate the efficacy of treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The nasal valves have been proposed to be a major regulator of nasal airflow, causing resistance and preventing airflow from exceeding the capacity to warm and humidify inspired air [2, 3]. The external nasal valve describes an area of the nasal vestibule bounded by the alar rim, nasal sill, and caudal septum [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Some commonly used procedures include batten grafts for external valve collapse and spreader grafts for internal valve compromise; other techniques include butterfly onlay grafts, alar rim grafts, suture suspension, and flaring sutures [210]. Accurate preoperative diagnosis of the specific anatomic problem and subsequent selection of the appropriate surgical technique will ensure the best possible results for patients undergoing functional rhinoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Further INVI surgery is often performed by several surgeons within an institution [11]. This case series adds valuable data to previously published work [5] and is one of the only case series performed by one operating surgeon. This provides consistency in technique unlike other series published.…”
Section: Discussionmentioning
confidence: 91%
“…Series are usually small [3] and involve several operating surgeons [4] without specific outcomes. Recent papers have called for a single technique by a single operating surgeon to be assessed [5]. …”
Section: Introductionmentioning
confidence: 99%